2018
DOI: 10.3847/2041-8213/aacaf3
|View full text |Cite
|
Sign up to set email alerts
|

The First Naked-eye Superflare Detected from Proxima Centauri

Abstract: Proxima b is a terrestrial-mass planet in the habitable-zone of Proxima Centauri. Proxima Centauri's high stellar activity however casts doubt on the habitability of Proxima b: sufficiently bright and frequent flares and any associated proton events may destroy the planet's ozone layer, allowing lethal levels of UV flux to reach its surface. In March 2016, the Evryscope observed the first naked-eyebrightness superflare detected from Proxima Centauri. Proxima increased in optical flux by a factor of ∼68 during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 56 publications
3
128
1
Order By: Relevance
“…If we assume the coplanarity of the orbits of the planets Proxima b and c, the de-projected mass of the close-in planet is m b = 2.1 +1.9 −0.6 M ⊕ (adopting m b sin i = 1.0±0.1 M ⊕ from Damasso et al 2020). It has been suggested that this planet is lying in the habitable zone of Proxima, but this red dwarf is known to experience strong flares (MacGregor et al 2018;Howard et al 2018). Vida et al (2019) recently observed repeated, very ener-getic events using the TESS (Transiting Exoplanet Survey Satellite).…”
Section: Discussionmentioning
confidence: 99%
“…If we assume the coplanarity of the orbits of the planets Proxima b and c, the de-projected mass of the close-in planet is m b = 2.1 +1.9 −0.6 M ⊕ (adopting m b sin i = 1.0±0.1 M ⊕ from Damasso et al 2020). It has been suggested that this planet is lying in the habitable zone of Proxima, but this red dwarf is known to experience strong flares (MacGregor et al 2018;Howard et al 2018). Vida et al (2019) recently observed repeated, very ener-getic events using the TESS (Transiting Exoplanet Survey Satellite).…”
Section: Discussionmentioning
confidence: 99%
“…Since survival curves to UVC are frequently biphasic, the effect produced by high fluences, like those expected during flares or superflares, cannot be appraised from the initial slope and from the total fluence imparted, such as previous studies assumed by using the UV-LD. For instance, some of them predicted no survival to superflares taking as parameter for lethality fluences greater than 553 Jm −2 (Howard et al 2018;Estrela & Valio 2018), which is, according to our experiments, roughly 70 times smaller than the fluence to produce a significant decrease in the viability of the microorganisms on Proxima b during a superflare. Moreover, previous theoretical studies using data from curves of UV-BAS for microorganisms (Rugheimer et al 2015;O'Malley-James & Kaltenegger 2017;Estrela & Valio 2018;O'Malley-James & Kaltenegger 2019) or DNA molecules in vitro (Buccino et al 2006(Buccino et al , 2007Rugheimer et al 2015) are missing important information, as they work with UV-BAS usually obtained at low fluences in contrast to those related to flares or superflares.…”
Section: Biological Effects Of Flaresmentioning
confidence: 65%
“…Although several studies have focused on stellar UVR aiming to evaluate the chances of an exoplanet to host life on its surface, they are based on modelling (see e.g. : Cockell 1999;Buccino et al 2006Buccino et al , 2007Fossati et al 2012;O'Malley-James & Kaltenegger 2017;Howard et al 2018;Estrela & Valio 2018;Rugheimer et al 2015;O'Malley-James & Kaltenegger 2019). Some of these approaches have neglected some important factors that may lead to: (i) an inaccurate estimation of the UV flux on ⋆ E-mail: abrevaya@iafe.uba.ar † Visiting scientist at the University of Graz the surface of the planet, as some studies do not assume the presence of a planetary atmosphere or assume unrealistic atmospheric compositions for the stellar spectral type and activity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With upcoming missions such as the James Webb Space Telescope (JWST), the European Extremely Large Telescope (E‐ELT), and/or the Atmospheric Remote‐sensing Infrared Exoplanet Large‐survey (ARIEL), we soon will be on the verge to detect and characterize atmospheres of Earth‐like exoplanets for the first time. Recent observations, however, showed that the exoplanetary radiation environment around certain K‐ and M‐dwarf stars, favored targets of these missions, is much harsher compared to what we know from the Sun (see, e.g., Howard et al, ). Today, we know that, e.g., the presence of strong stellar winds can lead to the erosion of unprotected planetary atmospheres (see, e.g., Cohen et al, ; Dong et al, ; Garcia‐Sage et al, ) and that extreme stellar particle events can cause drastic radiation dose increases, which may prevent the creation and development of life on Earth‐like exoplanets (see, e.g., do Nascimento et al, ; Vidotto et al, ).…”
Section: Discussionmentioning
confidence: 99%